THU0055 The Nuclear Receptor Vitamin D Receptor Regulates TGF-ß Signaling and Fibroblast Activation in Systemic Sclerosis. (23rd January 2014) - Zerr, P.; Vollath, S.; Palumbo-Zerr, K.; Tomcik, M.; Distler, A.; Beyer, C.; Dees, C.; Distler, O.; Schett, G.; Distler, J. H.
Abstract : Background: Vitamin D receptor (VDR) is a member of the nuclear receptor superfamily. Its ligand, 1, 25-(OH)2 D, is a metabolically active hormone derived from vitamin D3 . Activated VDR binds to specific VDR elements in the promoters of target genes to regulate their expression. The levels of vitamin D3 have been shown to be significantly decreased in patients with systemic sclerosis (SSc). However, the functional consequences remain unknown. Objectives: The aim of the present study was to investigate to investigate a potential link between impaired VDR signaling and fibrosis in SSc. Methods: The expression of VDR was analyzed by real-time PCR, Western Blot and immunohistochemistry. Collagen synthesis was quantified by real-time PCR, SirCol- and hydroxyproline assay. VDR signaling was modulated using the VDR agonist paricalcitol, siRNA mediated knockdown and knockout mice. The role of VDR was evaluated in cultured SSc fibroblasts and in two different mouse models: bleomycin-induced dermal fibrosis and mice infected with adenovirus overexpressing constitutively active TGFβ receptor I (TBR). The interaction of VDR and Smad3 was analyzed via Co-IP. Results: The mRNA levels of VDR were decreased by 78 % in the skin of SSc patients compared to healthy individuals (p = 0.02). Consistently, the protein levels of VDR were strongly reduced in SSc patients. Treatment of fibroblasts with TGFβ reduced VDR mRNA levels by 51% (p = 0.04) and decreased VDR expression on protein level. The collagen synthesis was upregulated in VDR knockout fibroblasts with 7.7 ± 0.78 fold increases in Col1a1 mRNA (p = 0.0001) and 3.2 ± 0.24 fold increases in collagen protein (p < 0.0001). Treatment of fibroblasts with the VDR agonist paricalcitol reduced Col1a1 mRNA to base line levels (p = 0.008) and decreased release of collagen protein by 72% (p = 0.03) compared to control fibroblasts upon TGFβ stimulation. Consistent with an anti-fibrotic role of VDR, mice treated with paricalcitol were less sensitive TBR induced dermal fibrosis with diminished dermal thickening (-46%, p = 0.008), myofibroblast counts (-69%, p = 0.0013) and hydroxyproline content (-77%, p = 0.02). Similar results with significant decreases in dermal thickening, myofibroblast counts and hydroxyproline content upon treatment with paricalcitrol were observed in bleomycin-induced dermal fibrosis. Co-IP revealed that VDR forms a high-affinity complex with active, phosphorylated Smad3, which prevents Smad3 dependent transcriptional activity. Treatment with paricalcitol stimulates the formation of VDR / phosphorylated Smad3 complexes to inhibit the transcription of TGFß target genes in fibroblasts. Conclusions: We demonstrate that VDR is a crucial regulator of TGFβ / Smad signaling. Pharmacological activation of VDR inhibits TGFβ signaling and reduces fibrosis. Impaired VDR signaling with reduced levels of its ligand vitamin D3 and decreased expression of VDR may thus contribute to hyper-active TGFβ signaling and aberrant fibroblast activation in SSc. These findings also may have direct clinical implications, considering the potent anti-fibrotic effects, the good tolerability and the availability of VDR agonists for clinical trials. Disclosure of Interest: None Declared